(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Megem О. М. Modernization of school biology education in Ukraine in the second half of the 60 ’s-mid 80-ies of the XX century. On the basis of the analysis of movement strategies of the social environment in the studied chronological framework identifies the leading landmarks in the development of school biology education. The influence of socio-political, socio-economic and ideological factors on the formation of substantive and methodological trends.